Postoperative outcome in thoracolumbar spinal tuberculosis: a retrospective study - Abu, Shaji U.; Kollannur, Lijo J.; K., Sreenath (International Journal of Research in Medical Sciences, 2020)
Background: Spinal tuberculosis is the most common location of extra pulmonary tuberculosis. ATT alone may not be suitable in all situations, especially when treating patients with risk of instability, progression of neurologic deficit, and failure of medical treatment. Surgical intervention is a major treatment modality for symptom relief in spinal tuberculosis. Methods: The aim of this study was to assess the immediate post-operative outcome in surgically treated patients with dorsolumbar spine tuberculosis at Department of Neurosurgery Government Medical College, Thrissur. All operated patients of dorsolumbar spinal tuberculosis during 2014 September to 2019 august were included under study. Results: A total of 57 patients were included in the study. The mean age of the patient was 42.77 years. There were 40 males (70.2%) and 17 females (29.8%). 55 (96.5%) out of 57 patients were having sensory symptoms. 41 (71.9%) out of 57 patients were having motor symptoms. Bladder involvement 23 (40.4%) and bowel involvement 15 (26.3%) were also noted in the study. Sensory symptoms improvement in post-operative period was noted in 46 (80.7%). Motor symptoms improvement was observed in 23 (56.1%) out of 41. Bladder symptoms improved in 6 (26.1%) out of 23. There is improvement in clinical symptoms, neurological function immediately after surgery. Surgical patients have faster improvement and can be mobilized earlier. Improvement in sensory symptoms (96.5%), motor symptoms (56.1%) and bladder symptoms (26.1%) were noted in our study in the immediate post-operative period. Conclusions: There was significant immediate relief in symptoms and morbidity of patients undergoing surgical treatment for dorsolumbar spine tuberculosis.